MICROSPHERES PREPARATION AND EVALUATION BY NATURAL GUM FOR ANTIVIRAL DRUG - Yashwant Singh; Kush Biswas; Siddharth Bajpai (EPRA International Journal of Research and Development (IJRD), 2022)
The present study shows the preparation and evaluation of microspheres of natural gum containing antiviral drug. Lamivudine is an active anti-retroviral drug. Compatibility study was carried out by using FTIR at the range of 800cm-1 to 3800cm-1 and shows no significant change in the characteristic peaks of Lamuvidine and excipients in all the formulation. Lamuvidine Microspheres is formed by solvent evaporation technique by using xanthan gum and guar gum as rate controlling agent. The Scanning Electron Microscopy (SEM) studies inferred the spherical shape and size range of formulations. In-vitro drug release shows decreases as concentration of xanthan gum increases and release rate was zero order and Fickian diffusion controlled. Stability studies were carried out which indicate that selected formulation was stable. We conclude that microspheres offer a practical and suitable approach to prepare controlled release of Lamuvidine with natural occurring xanthan gum as rate controlling agent to enhance bioavailability and reduction in dose frequency.